The Dualism of Organizational Behavior Research: Bridging Micro and Macro Perspectives for Future Theoretical Advancements - Hendro Wibowo; Rini Rahmawati; Ahmad Rifani (Citakonsultindo, 2025)
Organizational behavior (OB) research has long been shaped by dualisms, most notably the divide between micro-level analyses of individual and group behavior and macro-level investigations of organizational structures, culture, and leadership. While traditionally studied in isolation, recent global disruptions have underscored the need for an integrative perspective that transcends these boundaries. This study employs a systematic literature review (SLR) following PRISMA guidelines to synthesize findings from quantitative, qualitative, and mixed-methods research published between 2010 and 2024. Drawing on foundational and contemporary studies, we examine how micro-level constructs, such as emotional intelligence, job crafting, and adaptability, interact with macro-level dynamics, such as leadership style, structural design, and organizational culture to influence outcomes including effectiveness, psychological safety, and resilience. The analysis reveals that reciprocal micro-macro interactions are mediated by cultural and structural mechanisms and moderated by contextual variables, such as crisis conditions and digital work environments. We propose a dual-perspective theoretical framework that reconceptualizes OB as an emergent, co-constitutive process, bridging personal agency with institutional systems. This approach enhances theoretical clarity, enables cross-disciplinary integration, and informs the design of practical interventions that align individual development with systemic transformation. The paper concludes with recommendations for future research, emphasizing longitudinal designs, cross-cultural comparisons, and relational models as avenues for advancing holistic OB theory and practice. Keywords: Organizational behavior, micro-macro integration, emotional intelligence, leadership, job crafting, organizational structure, systematic literature review, dual-perspective framework